2023
DOI: 10.3390/genes14010161
|View full text |Cite
|
Sign up to set email alerts
|

LncPLAAT3-AS Regulates PLAAT3-Mediated Adipocyte Differentiation and Lipogenesis in Pigs through miR-503-5p

Abstract: Animal fat deposition has a significant impact on meat flavor and texture. However, the molecular mechanisms of fat deposition are not well understood. LncPLAAT3-AS is a naturally occurring transcript that is abundant in porcine adipose tissue. Here, we focus on the regulatory role of lncPLAAT3-AS in promoting preadipocyte proliferation and adipocyte differentiation. By overexpressing or repressing lncPLAAT3 expression, we found that lncPLAAT3-AS promoted the transcription of its host gene PLAAT3, a regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Plaat3's absence or divergence outside of mammals is also noteworthy, as it plays vital roles in obesity, cancer invasion and vitamin-A storage [57][58][59]. Remarkably, in the course of this work, we observed the venomous mammal Sorex araneus had more than 30 duplications of plaat3, which is also present in the salivary transcriptome of another venomous shrew, Blarina brevicauda, which suggests that plaat3 might have been recruited into the venom proteome in shrews.…”
Section: (E) Other Important Physiologiesmentioning
confidence: 57%
“…Plaat3's absence or divergence outside of mammals is also noteworthy, as it plays vital roles in obesity, cancer invasion and vitamin-A storage [57][58][59]. Remarkably, in the course of this work, we observed the venomous mammal Sorex araneus had more than 30 duplications of plaat3, which is also present in the salivary transcriptome of another venomous shrew, Blarina brevicauda, which suggests that plaat3 might have been recruited into the venom proteome in shrews.…”
Section: (E) Other Important Physiologiesmentioning
confidence: 57%
“…(41,(45)(46)(47) Furthermore, our data are in line with earlier studies suggesting a central role for PLAAT3 in adipocyte differentiation in several species. (19)(20)(21) A close link between PLAAT3 and PPARγ is supported by a murine adipocyte differentiation study demonstrating that Plaat3 mRNA levels started to increase between 6 and 12h after Pparγ-mediated initiation of differentiation. (19) A similar observation was made for human PLAAT3 transcripts whose expression began to rise 6h after induction of human pre-adipocyte differentiation and continued to increase during adipogenesis, like PPARγ, whose expression started a few hours earlier.…”
Section: Discussionmentioning
confidence: 93%
“…(5) Other studies have suggested an important role of PLAAT3 in adipocyte differentiation. (19)(20)(21) We used Plaat3 -/mice-derived inguinal WAT samples (7) for morphological and multiomics studies to further clarify the pathogenic mechanism of PLAAT3-related LS. In total, we collected 12 inguinal Plaat3 -/-WAT biopsy specimens and 12 Plaat3 +/inguinal WAT control specimens.…”
Section: Patients With Homozygous Plaat3 Null Variants Present With A...mentioning
confidence: 99%
“…Meanwhile, in pigs, for instance, PU.1 antisense lncRNA transcribed from porcine PU.1 inhibits the translation of PU.1 mRNA and promotes adipose production [33]. The lncRNA PLA2G16-AS regulates the expression of PLA2G16 by complementing the host gene, which plays an important role in porcine fat deposition [34,35]. In this paper, we explore the potential molecular mechanism of lncRNA G8110 in regulating adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%